An evaluation of learners' level of satisfaction using MOOC: satisfied or unsatisfied / Nurul Ain Hasni... [et al.] - Hasni, Nurul Ain; Kasmaruddin, Nurhidha Irawaty; Megat Abdul Rahim, Puteri Rohani; Ya Shak, Mohamad Syafiq; Abdul Malik, Norasyikin (UiTM Cawangan Johor, 2019)
Massive Open Online Course or MOOC has been blooming and most universities are offering MOOCs so as to remain relevant with the current education trend. MOOC is one of the most recent innovations in education that offers a lifelong learning opportunity and free short online courses available to anyone in the world. The current study aims to investigate the learners' perception and satisfaction level on the use of instructional design of MOOCs using a quantitative research design. The study was based on a survey questionnaire which was carried out randomly to 68 Diploma learners of UiTM Perak Branch. In addition, comments and suggestions from the participants were also analysed. The results revealed that the majority of the learners had high level of satisfaction in using MOOCs. The learners were found to be receptive given that the courses were free, interactive and easily accessible. The most appealing aspects that contributed towards the satisfaction level were teaching methods and the learning environment, whereas the least was on the assessment aspect. However, the learners also shared their concern as part of their suggestions on the issue of improvising the connectivity as well as timely feedback by the instructors. It is hoped that the findings of this study would be beneficial for future offerings of MOOCs which could incorporate these suggestions to improvise learning experiences and learners' satisfaction.